2022
DOI: 10.21203/rs.3.rs-2280847/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oridonin attenuates the progression of atherosclerosis by inhibiting NLRP3 and activating Nrf2 in apolipoprotein E-deficient mice

Abstract: Oridonin, a well-known traditional Chinese herbal medicinal product isolated from Isodon rubescens (Hemsl.) H.Hara, has many potential properties, including anti-inflammatory and antioxidant activities. However, there is no evidence whether oridonin have a protective effect on atherosclerosis. This study focused on the effects of oridonin on oxidative stress and inflammation generated from atherosclerosis. The therapeutic effect on atherosclerosis was evaluated by intraperitoneal injection of oridonin in a hig… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Very recently, Wang et al 43 demonstrated that oridonin exerted a therapeutic effect towards atherosclerosis through NACHT, LRR and PYD domain containing protein 3 (NLRP3) and nuclear factor E2-related factor 2 (Nrf2). Interestingly, growing evidence showed that FABP4/PPARγ exerted a regulatory role on NLRP3 and Nrf2.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Wang et al 43 demonstrated that oridonin exerted a therapeutic effect towards atherosclerosis through NACHT, LRR and PYD domain containing protein 3 (NLRP3) and nuclear factor E2-related factor 2 (Nrf2). Interestingly, growing evidence showed that FABP4/PPARγ exerted a regulatory role on NLRP3 and Nrf2.…”
Section: Discussionmentioning
confidence: 99%